Decreased expression levels of Ifi genes is associated to the increased resistance to spontaneous arthritis disease in mice deficiency of IL-1RA. (December 2016) - Liu, Xiaoyun; Jiao, Yan; Cao, Yanhong; Deng, Nan; Ma, Yonghui; Hasty, Karen; Kang, Andrew; Chen, Hong; Stuart, John; Gu, Weikuan
Abstract Background The mouse strain BALB/c deficient in IL-1 receptor antagonist protein (Il-1ra ) develops spontaneous arthritis disease (SAD) while the strain DBA/1IL1rn -/- with the same deficiency does not. Previously, we mapped a QTL on chromosome 1 for SAD and then developed a congenic mouse strain BALB.D1-1-/- that contains the QTL genomic fragment associated with resistance from DBA/1-/- on a BALB/c-/- background. The congenic strain was relatively resistant to spontaneous arthritis and had delayed onset and reduced severity of disease. We obtained whole genome expression profiles from the spleen of the congenic strain BALB.D1-1-/- and four other strains, the wild type BALB/c, DBA/1 and the deficient DBA/1IL1rn -/- and the BALB/cIL1rn -/- . We then compared the similarities and differences between the congenic strain and the four parental strains. Here we report the selected potential causal genes based on differential expression levels as well as function of genes. Results There is a considerable number of genes that are differentially expressed between the congenic strain and the three parental strains, BALB/c, DBA/1, and DBA/1-/- . However there only a few differentially expressed genes were identified by comparing the congenic strain and the BALB/c-/- strain. These differentially expressed genes are mainly from T-cell receptor beta chain (Tcrb ) and interferon-activatable protein (Ifi ) genes. These genes are also differentially expressed between congenic strain and BALB/c strains. However, their expression levels in the congenic strain are similar to that in DBA/1 and DBA/1-/- . The expression level ofTcrb-j gene is positively associated with two genes ofIfi gene 200 cluster. Conclusions Decreased expression levels ofIfi genes is associated to the increased resistance to spontaneous arthritis disease and with down regulation of expressions ofTcrb genes in the mouse congenic strain.Ifi genes may play an important role in the susceptibility to SAD in mice.